Fluorescent glasses with high content of cerium and tin

By adjusting the formula and molar ratio in the glass, the problem that existing glass cannot simulate natural tooth fluorescence properties under long-wave ultraviolet light is solved, and a more natural appearance of tooth restoration materials is achieved.

JP2025048807APending Publication Date: 2025-04-03IVOCLAR VIVADENT AG
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024162352
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-20
Filing Date
2024-09-19
Publication Date
2025-04-03

AI Technical Summary

Technical Problem

Existing glasses cannot effectively simulate the fluorescent properties of natural teeth in the long-wave ultraviolet range (380-430 nm), resulting in dental restoration materials that may be mistaken for tooth defects or unnatural under specific lighting conditions.

Method used

Using a glass formula with high content of actinium lithium and tin, the fluorescence performance of glass under long-wave ultraviolet light is improved, making it closer to the fluorescence characteristics of natural teeth by adjusting the content and molar ratio of actinium lithium and tin.

Benefits of technology

The fluorescence performance of glass is significantly improved under long-wave ultraviolet light, allowing it to more effectively simulate the appearance of natural teeth, and solve the problem that existing materials are mistaken for tooth defects under specific lighting conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025048807000004
    Figure 2025048807000004
  • Figure 2025048807000001
    Figure 2025048807000001
  • Figure 2025048807000002
    Figure 2025048807000002
Patent Text Reader

Abstract

To provide fluorescent glasses with high content of cerium and tin.SOLUTION: The invention relates to glasses with high content of cerium and tin. The glasses contain the following components: 38.0 to 68.0 wt.% of SiO2; 4.0 to 23.0 wt.% of cerium, calculated as CeO2; 3.0 to 18.0 wt.% of tin, calculated as SnO; 1.0 to 5.0 wt.% of Li2O; 5.8 to 15.9 wt.% of alkali metal oxide MeI2O; 3.2 to 10.5 wt.% of oxide of divalent elements MeIIO; and 3.5 to 11.8 wt.% of oxide of trivalent elements MeIII2O3. The glasses are particularly suitable for the preparation of dental restorations with fluorescence properties largely corresponding to those of natural teeth.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass which has a high content of cerium and tin and is particularly suitable for the preparation of dental restorations whose fluorescence properties correspond largely to those of natural teeth. The present invention also relates to a process for preparing the glass according to the invention and to the use of the glass according to the invention as a mixed component and as a dental material, in particular as a coating material for the preparation of dental restorations. [Background technology]

[0002] Due to their good optical properties, glasses are used in particular in dentistry for coating other materials, for example as stains or polishes.

[0003] Various approaches are known for reproducing the fluorescent properties of natural teeth in glasses and, where appropriate, glass-ceramics made from glasses in the preparation of dental restorations.

[0004] EP 2 944 619 A1 describes a process for the preparation of fluorescent lithium silicate glasses, which comprises subjecting a melt of a starting glass containing cerium ions to reducing conditions, which are provided by the use of a reducing agent, which is preferably a gaseous reducing agent or is selected from the group consisting of organic salts, carbohydrates and cereal flours.

[0005] WO 2017 / 032745 A1 describes low-quartz glass-ceramics of lithium silicate for use in dentistry, which contain fluorescent and coloring agents, preferably selected from Bi2O3 and Bi2O5, as well as inorganic pigments and / or oxides of d and f elements, such as the oxides of Mn, Fe, Co, Pr, Nd, Tb, Er, Dy, Eu and Yb.

[0006] From EP 3 696 150 A1 it is known that glasses containing 0.05 to 5.0% by weight of europium, calculated as Eu2O3, impart advantageous fluorescence properties to dental restorations made from these glasses.

[0007] It is known from W. Buchalla, “Comparative Fluorescence Spectroscopy Shows Differences in Non-Cavitated Enamel Lesions,” Caries Res. 2005, 39, 150-156 that natural teeth exhibit bluish-white fluorescence under ultraviolet light having a wavelength in the range of 400-650 nm. EP 3 696 149 A1 describes glasses and glass ceramics containing cerium and tin that fluoresce when excited with light of a wavelength of 365 nm. However, when excited with light of a wavelength of 395 nm, the glasses and glass ceramics described do not show any fluorescence. It has been shown that glasses known from the prior art have poor fluorescence properties and are unable to adequately mimic the fluorescence properties of natural tooth materials, especially under light with a wavelength of about 380-430 nm. In particular, there is a need for glasses that also exhibit good fluorescence properties, especially in the long-wave UV range, for example 380-430 nm. Light of these wavelengths is often used as "black light" in entertainment venues such as nightclubs. Thus, dental restorations with poor fluorescence properties may be recognized as restorations under the influence of long-wave UV light, or may appear to be gaps or defects in teeth. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] European Patent Application Publication No. 2 944 619 [Patent Document 2] International Publication No. 2017 / 032745 [Patent Document 3] European Patent Application Publication No. 3 696 150 [Patent Document 4] European Patent Application Publication No. 3 696 149 [Non-patent literature]

[0009] [Non-Patent Document 1] W. Buchalla, “Comparative Fluorescence Spectroscopy Shows Differences in Non-Cavitated Enamel Lesions,” Caries Res.2005,39,150-156 Summary of the Invention [Means for solving the problem]

[0010] The present invention is based on the problem of providing glasses which exhibit a fluorescence comparable to that of natural tooth materials and are therefore particularly suitable for the preparation of dental restorations which are able to largely mimic the fluorescence properties of natural tooth materials when excited in the long-wave UV range, for example 380-430 nm, and especially 395 nm. These glasses should also be suitable as mixing components for adjusting the fluorescence properties of other glasses.

[0011] This problem is solved according to the invention by the cerium- and tin-containing glasses of claims 1 to 12, as well as by the glasses and glass-ceramics comprising the glasses according to the invention of claim 13. The invention also relates to the use of the glasses according to claims 16 and 17. Furthermore, the invention relates to processes for preparing the glasses according to claims 14 and 15, as well as to a coating process using the glasses according to claim 18.

[0012] The present invention provides, for example, the following items. (Item 1) A glass containing cerium and tin comprising the following components in the amounts indicated: Ingredients Weight% SiO238.0~68.0 Cerium calculated as CeO2 4.0~23.0 Tin calculated as SnO 3.0-18.0 Li2O 1.0~5.0 Alkali metal oxide Me I 2O 5.8~15.9 Divalent element oxide Me II O 3.2~10.5 Oxides of trivalent elements Me III 2O33.5~11.8 wherein Me I 2O is selected from Na2O, KO, Rb2O, and / or CsO; Me II O is selected from MgO, CaO, SrO, BaO and / or ZnO; Me III 2O3 is selected from Al2O3, B2O3, Y2O3, La2O3, Dy2O3, Ga2O3, and / or In2O3. (Item 2) The glass according to any one of the preceding items, containing 4.3 to 22.0 wt.-%, preferably 4.7 to 21.5 wt.-%, and more preferably 5.3 to 21.0 wt.-% cerium, calculated as CeO2. (Item 3) 5. The glass according to claim 1, containing 3.4 to 17.2% by weight, preferably 3.7 to 16.9% by weight and particularly preferably 4.1 to 16.4% by weight of tin, calculated as SnO. (Item 4) The glass according to any one of the preceding items, wherein the molar ratio of cerium, calculated as CeO2, to tin, calculated as SnO, is in the range of from 1.5:1 to 1:1.5, in particular from 1.2:1 to 1:1.2, preferably from 1.1:1 to 1:1.1, and more preferably is 1.0:1.0. (Item 5) %. The glass according to any one of the preceding items, containing 1.4 to 4.0 wt.-%, and particularly preferably 1.9 to 3.1 wt.-%, Li2O. (Item 6) 5. The glass according to claim 1, containing 0.4 to 2.4% by weight, in particular 0.6 to 1.9% by weight and particularly preferably 0.8 to 1.6% by weight of fluorine. (Item 7) The indicated amounts of the following alkali metal oxides: Ingredients Weight% K2O 2.0~7.9 Especially 2.5~7.3 Particularly preferably, 2.9 to 6.9 Na2O 3.8~8.0 Especially 4.4~7.4 Particularly preferably, 4.8 to 7.0 2. The glass according to claim 1, further comprising at least one, and preferably all, of: (Item 8) The indicated amounts of the oxides of the following divalent elements Me II O: Ingredients Weight% CaO 0.8~2.5 Especially 1.0~2.0 Particularly preferably, 1.2 to 1.7 SrO 1.0~3.0 Especially 1.3~2.6 Particularly preferably, 1.6 to 2.3 ZnO 1.4~4.0 Especially 1.9~3.6 Particularly preferably, 2.3 to 3.3 MgO 0~1.0 Preferably 0 to 0.6 Especially 0~0.4 Particularly preferably, 0.1 to 0.4 2. The glass according to claim 1, further comprising at least one, and preferably all, of: (Item 9) Oxides of the following trivalent elements in the amounts indicated: Ingredients Weight% Al2O3 2.5~7.3 Especially 2.8~6.8 Particularly preferably, 3.2 to 6.3 B2O31.0~4.5 Especially 1.3~4.1 Particularly preferably, 1.6 to 3.7 2. The glass according to claim 1, further comprising at least one, and preferably all, of: (Item 10) The indicated amounts of oxides of the following tetravalent elements Me IV O2: Ingredients Weight% TiO20~2.2 Especially 0~1.7 Particularly preferably, 0.1 to 1.4 ZrO20~1.2 Preferably 0.1 to 1.2 Especially 0.2~0.9 Particularly preferably, 0.4 to 0.6 2. The glass according to claim 1, further comprising at least one, and preferably all, of: (Item 11) Pentavalent element oxide Me V 2O5 in an amount of 0 to 10.0% by weight, particularly 0 to 8.0% by weight, preferably 1.0 to 7.0% by weight, more preferably 2.0 to 6.8% by weight, and particularly preferably 3.0 to 6.5% by weight, wherein the Me V 2O5 is in particular selected from P2O5, Ta2O5 and / or Nb2O5. (Item 12) The following ingredients in the amounts indicated: Ingredients Weight% SiO238.0~68.0 Cerium calculated as CeO2 4.0~23.0 Tin calculated as SnO 3.0-18.0 Li2O 1.0~5.0 Al2O3 2.5~7.3 Na2O 3.8~8.0 K2O 2.0~7.9 CaO 0.8~2.5 SrO 1.0~3.0 ZnO 1.4~4.0 B2O31.0~4.5 F 0.4~2.4 ZrO20~1.2 MgO 0~1.4 TiO20~3.0 2. The glass according to claim 1, further comprising at least one, and preferably all, of: (Item 13) Glasses and glass ceramics comprising the cerium- and tin-containing glass according to any one of the preceding items, preferably in an amount of 0.1 to 60% by weight, in particular 1 to 58% by weight, preferably 5 to 56% by weight, more preferably 10 to 54% by weight, and particularly preferably 15 to 52% by weight. (Item 14) 2. A process for preparing a glass according to claim 1, wherein the tin is used at least partly in divalent form, in particular as SnO. (Item 15) 2. The process according to claim 1, wherein the starting materials of the components of the glass are melted at a temperature of 1400° C. to 1700° C., in particular 1450 to 1600° C., and particularly preferably 1500° C., for a period of preferably 20 minutes to 10 hours. (Item 16) 2. Use of a glass according to any one of the preceding items as a mixture component for adjusting the fluorescence of a glass or glass ceramic. (Item 17) 13. Use of a glass according to any one of the preceding items as a dental material, in particular for coating dental restorations, in which the glass is applied to a substrate material and together with the substrate material is subjected to a heat treatment, preferably at a temperature of at least 600° C., in particular 600-1150° C. and particularly preferably 700-1000° C. (Item 18) 2. A process for coating dental restorations, in which a glass according to any one of the preceding items is applied to a substrate material and, together with said substrate material, is subjected to a heat treatment, preferably at a temperature of at least 600° C., in particular 600-1150° C. and particularly preferably 700-1000° C. [Brief description of the drawings]

[0013] [Figure 1] The object shown on the right side of Figure 1 is a fluorescent glass body when irradiated with a UV LED. The object on the left side of Figure 1 is the resulting solid glass sheet, which does not exhibit fluorescence when irradiated with a UV LED. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] Description of the embodiments The present invention relates to a method for producing a composition comprising the following components: Ingredients Weight% SiO238.0~68.0 Cerium calculated as CeO2 4.0~23.0 Tin calculated as SnO 3.0-18.0 Li2O 1.0~5.0 Alkali metal oxide Me I 2O 5.8~15.9 Divalent element oxide Me II O 3.2~10.5 Oxides of trivalent elements Me III 2O33.5~11.8 and relates to glasses with a high content of cerium and tin which are particularly suitable for the preparation of dental restorations whose fluorescence properties correspond largely to those of natural teeth.

[0015] The present invention comprises the following components in the amounts indicated: Ingredients Weight% SiO238.0~68.0 Cerium calculated as CeO2 4.0~23.0 Tin calculated as SnO 3.0-18.0 Li2O 1.0~5.0 Alkali metal oxide Me I 2O 5.8~15.9 Divalent element oxide Me II O 3.2~10.5 Oxides of trivalent elements Me III 2O33.5~11.8, wherein Me I 2O is selected from Na2O, KO, Rb2O, and / or CsO; Me II O is selected from MgO, CaO, SrO, BaO and / or ZnO; Me III 2O3 is selected from Al2O3, B2O3, Y2O3, La2O3, Dy2O3, Ga2O3 and / or In2O3 The present invention relates to a glass containing cerium and tin, characterized in that

[0016] Surprisingly, it has been shown that the glasses according to the invention exhibit improved fluorescence properties compared to the prior art, in particular when exposed to UV light having a wavelength between 380 and 430 nm, for example 395 nm. In the context of the present invention, it has been found that the use of higher amounts of cerium and tin than known in the prior art causes a change in the fluorescence properties of the glass. In particular, it has been shown that by using a higher proportion of cerium and tin, a clearly visible fluorescence can be obtained, even when excited with light having a wavelength between 380 and 430 nm. It has therefore been shown that the glasses according to the invention are particularly suitable for imitating natural tooth materials.

[0017] Without being limited to any particular theory, it is believed that the use of higher amounts of cerium and tin results in a higher yield of Ce 3+It is hypothesized that this changes the fluorescence properties of the ions and shifts the excitation spectrum, so that a clear fluorescence can also be perceived in the glass when excited with light of a wavelength in the range of 380-430 nm, for example 395 nm. The high intensity of fluorescence observed in the glass according to the invention when excited with light of a wavelength of 380-430 nm is surprising, since the glasses known in the prior art, such as in particular those described in EP 3 696 149, do not show any perceptible fluorescence when excited in this way.

[0018] The glass according to the invention preferably contains 4.3 to 22.0% by weight, in particular 4.7 to 21.5% by weight and particularly preferably 5.3 to 21.0% by weight of cerium, calculated as CeO2.

[0019] It is also preferred that the glass contains 3.4 to 17.2% by weight, in particular 3.7 to 16.9% by weight and particularly preferably 4.1 to 16.4% by weight of tin, calculated as SnO.

[0020] According to the invention, preference is also given to glasses in which the molar ratio of cerium, calculated as CeO2, to tin, calculated as SnO, is in the range from 1.5:1 to 1:5, in particular from 1.2:1 to 1:1.2, more preferably from 1.1:1 to 1:1.1 and particularly preferably 1.0:1.0.

[0021] According to the invention, it is also preferred that the glass contains 40.0 to 65.0% by weight, and particularly preferred 42.0 to 62.0% by weight, of SiO2.

[0022] It is also preferred that the glass contains 1.4 to 4.0 wt. % Li2O, and more preferably 1.9 to 3.1 wt. %.

[0023] In another preferred embodiment, the glass contains 0.4 to 2.4% by weight, in particular 0.6 to 1.9% by weight and particularly preferably 0.8 to 1.6% by weight of fluorine.

[0024] In a preferred embodiment, the glass contains 6.9 to 14.7% by weight, and in particular 7.7 to 13.9% by weight, of alkali metal oxide Me I 2O, where Me I 2O is selected from Na2O, K2O, Rb2O and / or Cs2O, and in particular from Na2O and / or K2O.

[0025] Preferably, the glass according to the invention contains the following alkali metal oxides Me in the amounts indicated: I 2O: Ingredients Weight% K2O 2.0~7.9 Especially 2.5~7.3 Particularly preferably, 2.9 to 6.9 Na2O 3.8~8.0 Especially 4.4~7.4 Particularly preferably, 4.8 to 7.0 It contains at least one, particularly all, of:

[0026] In a further preferred embodiment, the glass contains 4.2 to 8.8 wt. %, and in particular 5.1 to 7.7 wt. %, of oxides of divalent elements Me II O, where Me II O is selected from MgO, CaO, SrO, BaO and / or ZnO, and preferably selected from MgO, CaO, SrO and / or ZnO.

[0027] The glasses contain the following oxides of divalent elements in the amounts shown: II O: Ingredients Weight% CaO 0.8~2.5 Especially 1.0~2.0 Particularly preferably, 1.2 to 1.7 SrO 1.0~3.0 Especially 1.3~2.6 Particularly preferably, 1.6 to 2.3 ZnO 1.4~4.0 Especially 1.9~3.6 Particularly preferably, 2.3 to 3.3 MgO 0~1.0 Preferably 0 to 0.6 Especially 0~0.4 Particularly preferably, 0.1 to 0.4 It is particularly preferred to contain at least one, and in particular all, of:

[0028] The glass contains 4.1 to 10.9% by weight, and in particular 4.8 to 10.0% by weight, of oxides of trivalent elements Me III It is also preferred that the compound contains Me. III 2O3 is selected from Al2O3, B2O3, Y2O3, La2O3, Dy2O3, Ga2O3 and / or In2O3, and preferably selected from Al2O3 and / or B2O3.

[0029] In particularly preferred embodiments, the glass contains the following oxides of trivalent elements Me III 2O3: Ingredients Weight% Al2O3 2.5~7.3 Especially 2.8~6.8 Particularly preferably, 3.2 to 6.3 B2O31.0~4.5 Especially 1.3~4.1 Particularly preferably, 1.6 to 3.7 It contains at least one, particularly all, of:

[0030] The glass contains 0.1 to 3.4% by weight, in particular 0.2 to 2.6% by weight, and more preferably 0.4 to 2.0% by weight of oxides of tetravalent elements Me IV It is also preferred to further contain O2, where Me IV O2 is selected from ZrO2, TiO2 and / or GeO2, and preferably is selected from ZrO2 and / or TiO2.

[0031] Particularly preferably, the glass contains the following oxides of tetravalent elements Me IV O2: Ingredients Weight% TiO20~2.2 Especially 0~1.7 Particularly preferably, 0.1 to 1.4 ZrO20~1.2 Preferably 0.1 to 1.2 Especially 0.2~0.9 Particularly preferably, 0.4 to 0.6 It contains at least one, particularly all, of:

[0032] In a preferred embodiment, the glass is made of an oxide of a pentavalent element, Me V 2O5 in an amount of 0 to 10.0% by weight, in particular 0 to 8.0% by weight, preferably 1.0 to 7.0% by weight, more preferably 2.0 to 6.8% by weight, and particularly preferably 3.0 to 6.5% by weight, wherein the Me V 2O5 is in particular selected from P2O5, Ta2O5 and / or Nb2O5, and particularly preferably selected from P2O5 and / or Ta2O5.

[0033] According to the invention, the glass comprises the following components in the amounts indicated: Ingredients Weight% SiO238.0~68.0 Cerium calculated as CeO2 4.0~23.0 Tin calculated as SnO 3.0-18.0 Li2O 1.0~5.0 Al2O3 2.5~7.3 Na2O 3.8~8.0 K2O 2.0~7.9 CaO 0.8~2.5 SrO 1.0~3.0 ZnO 1.4~4.0 B2O31.0~4.5 F 0.4~2.4 ZrO20~1.2 MgO 0~1.4 TiO20~3.0 It is preferred to contain at least one, and preferably all, of the following:

[0034] The glass contains the following components in the amounts indicated: Ingredients Weight% SiO240.0~65.0 Cerium calculated as CeO2 4.3~22.0 Tin calculated as SnO 3.4-18.0 Li2O 1.4~4.0 Al2O32.8~6.8 Na2O 4.4~7.4 K2O 2.5~7.3 CaO 1.0~2.0 SrO 1.3~2.6 ZnO 1.9~3.6 B2O3 1.3~4.1 F 0.6~1.9 ZrO20.2~0.9 MgO 0~0.8 TiO20~2.0 It is further preferred to contain at least one, and preferably all, of:

[0035] In a particularly preferred embodiment, the glass comprises the following components in the amounts shown: Ingredients Weight% SiO242.0~62.0 Cerium calculated as CeO2 4.7~21.0 Tin calculated as SnO 3.7-17.2 Li2O 1.9~3.1 Al2O33.2~6.3 Na2O 4.8~7.0 K2O 2.9~6.9 CaO 1.2~1.7 SrO 1.6~2.3 ZnO 2.3~3.3 B2O31.6~3.7 F 0.8~1.6 ZrO20.4~0.6 MgO 0~0.4 TiO20~1.4 It contains at least one, preferably all, of:

[0036] The invention further relates to a glass according to the invention, which exhibits a whitish blue fluorescent colour in the CIE colour space when excited with light having a wavelength of 380 to 430 nm, in particular 395 nm.

[0037] The invention also relates to a process for the preparation of the glass according to the invention, in which tin is used in divalent form, in particular as SnO.

[0038] In the preparation of the glasses according to the invention, particularly suitable starting materials, such as mixtures of carbonates, oxides, phosphates and fluorides, are melted. In a preferred embodiment, the starting materials of the components of the glass are melted at temperatures of 1400-1700° C., in particular 1450-1600° C. and particularly preferably 1500° C., for preferably 20 min to 10 h.

[0039] The melt can then be added to water to produce granules. To achieve a particularly high degree of homogeneity, the granules can be melted again and the melt can be added again to water to form glass granules.

[0040] The glass granules are preferably comminuted into a powder, for example by grinding in a zirconium oxide mill. Further components, for example colorants, can be added to the powder. The powder can then be used, for example, to produce a powder mixture, a paste or an aerosol. Thus, the glass according to the invention is preferably in the form of a granule, a powder, a paste or an aerosol.

[0041] The glasses can also be used as blending components for blending into other glasses and glass ceramics, preferably into other glasses.

[0042] Glasses and glass ceramics containing the glass according to the invention therefore constitute further subject matter of the invention. Particularly preferred are glasses and glass ceramics which contain the glass according to the invention with a high content of cerium and tin in an amount of 0.1 to 60% by weight, in particular 1 to 58% by weight, preferably 5 to 56% by weight, particularly preferably 10 to 54% by weight and more preferably 5 to 52% by weight, based on the total amount of glass or glass ceramic and glass according to the invention. The invention also relates to the use of the glass with a high content of cerium and tin according to the invention as a mixture component for adjusting the fluorescence of glasses and glass ceramics.

[0043] The glasses with high contents of cerium and tin according to the invention can in particular be used in combination with various other glasses and glass ceramics, and these combinations can in particular be used as dental materials. It is preferred to use the glasses according to the invention in combination with other glasses. Particularly preferably, these combinations can be in the form of granules, powders, pastes, aerosols, or coatings for dental restorations. Examples of other glasses for preparing the combinations are DE 43 14 817 A1, DE 44 23 793 C1, DE 44 23 794 C1, DE 44 28 839 A1, DE 196 47 739 A1, DE 197 25 552 A1, DE 100 31 431 A1, EP 0 827 941 A1, EP 0 916 625 A1, WO 00 / 34196 A2, EP 1 505 041 A1, EP 1 688 398 A1, EP 2 287 122 A1, EP 2 377 831 A1, EP 2 407 439 A1, WO 2013 / 053863 A2, WO No. 2013 / 053864 A2, WO 2013 / 053865 A2, WO 2013 / 053866 A2, WO 2013 / 053867 A2, WO 2013 / 053868 A2, WO 2013 / 164256 A1, WO 2014 / 170168 A1, WO 2014 / 170170 A2, WO 2015 / 067643 A1, WO 2015 / 155038 A1, WO 2015 / 173394 A1, WO 2016 / 120146 A1, WO 2017 / 032745 A1, WO 2017 / 055010 A1. These glasses belong to the silicate, borate, phosphate or aluminosilicate groups. Preferred glasses are of the SiO2-Al2O3-K2O type, the SiO2-B2O3-Na2O type, the alkali silicate type, the alkali zinc silicate type, the silicophosphate type and / or the SiO2-ZrO2 type. Preferred glass ceramics for the mixture of glasses according to the invention to prepare the combination are apatite-containing glass ceramics.By mixing such glasses and glass ceramics with the glasses according to the invention having high contents of cerium and tin, in particular the fluorescent properties can be adjusted in a desired manner.

[0044] The glass ceramics according to the invention and the glasses according to the invention are also suitable, especially in the form of combinations, in particular for coating ceramics, glass ceramics and metals, for example. "Coatings" which can be produced using the glasses according to the invention and the glass ceramics according to the invention, especially in the form of combinations, also mean, for example, glazes.

[0045] The present invention therefore also relates to the use of the glass according to the invention and the glass ceramic according to the invention, in particular in the form of a combination, in particular for coating ceramics, glass ceramics and metals. The coating preferably comprises applying the glass according to the invention or the glass ceramic according to the invention, in particular in the form of a combination, to a substrate material and subjecting this together with the substrate material to a heat treatment at a temperature of at least 600° C., in particular from 600 to 1150° C. and particularly preferably from 700 to 1000° C.

[0046] Due to the above-mentioned properties of the glasses according to the invention, they are particularly suitable for use in dentistry. It is therefore also an object of the invention to use the glasses according to the invention as dental materials, in particular in the form of combinations.

[0047] The glasses according to the invention, especially in the form of combinations, can be used to coat dental restorations, in particular inlays, onlays, crowns, partial crowns, bridges, veneers, occlusal facets or abutments. The glasses according to the invention can therefore also be present as coatings on dental restorations.

[0048] The invention also relates to the use of the glass according to the invention for coating dental restorations, in which a substrate material, in particular a glass-ceramic, ceramic or metal, is coated with the glass according to the invention.

[0049] The use for coating dental restorations preferably involves applying the glass according to the invention, in particular in the form of a combination, to a substrate material and subjecting it together with the substrate material to a heat treatment, preferably at a temperature of at least 600° C., in particular 600-1150° C. and particularly preferably 700-1000° C. The application of the glass according to the invention, in particular in the form of a combination, is carried out in the usual manner, for example as a powder, paste or aerosol. Preferably, the substrate material is a glass ceramic, a ceramic or a metal.

[0050] The invention also relates to a process for coating dental restorations, in which a substrate material, in particular a glass-ceramic, ceramic or metal, is coated with a glass according to the invention. According to the invention, the glass can also be present in combination with a glass or glass-ceramic, for example an apatite-containing glass-ceramic.

[0051] The process for coating dental restorations preferably comprises applying the glass according to the invention, in particular in the form of a combination, to a substrate material and subjecting it together with the substrate material to a heat treatment, preferably at a temperature of at least 600° C., in particular 600-1150° C. and particularly preferably 700-1000° C. The application of the glass according to the invention, in particular in the form of a combination, is carried out in the usual manner, for example as a powder, paste or aerosol. Preferably, the substrate material is a glass ceramic, a ceramic or a metal.

[0052] The coating of the dental restoration is preferably carried out as part of the preparation of a coated dental restoration, in particular selected from inlays, onlays, crowns, partial crowns, bridges, veneers, occlusal facets and abutments.

[0053] The use of the glasses according to the invention in the preparation of coated dental restorations, in which a substrate material, in particular a glass-ceramic, ceramic or metal, is coated with a glass according to the invention, is therefore a subject of the present invention.

[0054] Furthermore, the present invention relates to a process for preparing coated dental restorations, in which a substrate material, in particular a glass-ceramic, ceramic or metal, is coated with a glass according to the invention.

[0055] The invention is explained in more detail below by means of examples, which do not limit the invention. EXAMPLES

[0056] 1. Preparation of fluorescent glass

[0057] Ten glasses according to the invention were prepared, with the compositions given in Table I. For this purpose, the starting glasses with the compositions given in Table I were first melted from common raw materials at 1500° C. for 60 minutes. A glass frit was prepared by pouring the molten starting glasses into water.

[0058] For glasses 1, 2, 4 and 8 according to the invention, the glass transition temperatures T g was determined by DSC (differential scanning calorimetry).

[0059] Furthermore, two glasses were produced using the corresponding process as comparative examples, the compositions of which are also given in Table I as Examples 11 and 12. In deviation from the process for the preparation of the glasses of Examples 1 to 10, the melting for the preparation of Example 11 was carried out at 1650° C. for 240 minutes.

[0060] The fluorescence properties of the glass frits were investigated. For this purpose, the glass frits were irradiated in turn with a mercury lamp (excitation wavelength 365 nm) and with a UV LED (excitation wavelength 395 nm) and examined in each case with the naked eye for fluorescence.

[0061] For the glass frits of Examples 1-10, clear fluorescence was perceptible both with mercury lamp excitation and with UV LED excitation.

[0062] The glass frit of Example 11 showed clearly perceptible fluorescence when irradiated with a mercury lamp (excitation wavelength 365 nm), but no perceptible fluorescence when excited with a UV LED (excitation wavelength 395 nm). Testing of the glass frit of Example 12 showed that no fluorescence was observed when irradiated with either a mercury lamp or a UV LED.

[0063] The glass frit of Example 2 was ground in a zirconium oxide mill to a particle size of 45 μm and sintered at 760° C. with a holding time of 1 minute. The glass body thus obtained showed a clearly perceptible whitish-blue fluorescence when irradiated with a UV LED (excitation wavelength 395 nm). This is also illustrated by the photograph shown as FIG. 1. The object shown on the right side of FIG. 1 is the fluorescent glass body when irradiated with a UV LED.

[0064] For comparison, a solid glass sheet was made from the glass frit of Example 11 by using the process described in EP 3 696 149 A1 for Example 5 thereof. This process included melting the glass frit of Example 11 again at 1650°C for 240 minutes. The resulting melt was then poured onto a copper block to produce a solid glass sheet. This solid glass sheet was then tested for its fluorescence when irradiated with a UV LED (excitation wavelength 395 nm). The results are also illustrated by Figure 1. The object on the left in Figure 1 is the resulting solid glass sheet, which does not show fluorescence when irradiated with a UV LED. [Table 1] 2. Use of fluorescent glass as a blend component

[0065] The glass frits of Examples 1, 4 and 12 were ground in a zirconia mill to a particle size of 45-90 μm. The ground glass frits of Examples 1 and 4 were then added as mixed components to the ground non-fluorescent glass frit of Example 12 in various amounts (20 wt %, 33 wt % and 50 wt % for the glass frit of Example 1; 33 wt % and 50 wt % for the glass frit of Example 4, based on the mixture).

[0066] 2.5 g of each powder mixture was mixed with 1.6 μl of distilled water and pressed in a hydraulic press at 25 bar for 10 seconds to form a compact, then heated to a temperature T Sinter and retention time t Sinter It was sintered at . [Table 2]

[0067] After sintering, the fluorescence properties of the sintered compacts were investigated under mercury lamp (excitation wavelength 365 nm) and UV LED (excitation wavelength 395 nm). The sintered compacts showed clearly perceptible fluorescence both when irradiated with mercury lamp and when irradiated with UV LED. It was found that strong fluorescence can be obtained by using high percentages of fluorescent mixture components. 3. Generation of sintered compact

[0068] The glass frits of Examples 1, 2 and 4 were milled in a zirconium oxide mill to a particle size of 45-90 μm. 2.5 g of each of the resulting glass powders was mixed with 1.6 μl of distilled water and pressed into blanks at 25 bar for 10 seconds using a hydraulic press and sintered in a sintering furnace at a temperature of T Sinter and retention time t Sinter It was sintered at .

[0069] The sintering conditions T used for the preparation of each blank Sinter and t Sinter is given in Table III. [Table 3]

[0070] The fluorescence of the obtained objects was determined under mercury vapor lamp (excitation wavelength 365 nm) and UV LED (excitation wavelength 395 nm). All sintered glasses showed clearly perceptible fluorescence when irradiated with mercury vapor lamp and also when irradiated with UV LED.

Claims

1. A glass containing cerium and tin comprising the following components in the amounts indicated: Ingredients Weight% Yes 2 38.0~68.0 CeO 2 Cerium calculated as 4.0-23.0 Tin calculated as SnO 3.0-18.0 Li 2 O 1.0~5.0 Alkali metal oxide Me I 2 O 5.8-15.9 Oxide of divalent element Me II O 3.2-10.5 Oxides of trivalent elements Me III 2 O 3 3.5 to 11.8 wherein Me I 2 O is Na 2 O.K. 2 O, Rb 2 O, and / or Cs 2 is selected from O, Me II O is selected from MgO, CaO, SrO, BaO and / or ZnO; Me III 2 O 3 is Al 2 O 3 , B 2 O 3 , Y 2 O 3 , La 2 O 3 , Dy 2 O 3 , Ga 2 O 3 and / or In 2 O 3 Selected from: glass.

2. 4.3 to 22.0 wt.%, preferably 4.7 to 21.5 wt.%, and more preferably 5.3 to 21.0 wt.% CeO 2 2. The glass of claim 1 , containing cerium, calculated as:

3. 3. The glass according to claim 1, which contains from 3.4 to 17.2% by weight, preferably from 3.7 to 16.9% by weight and particularly preferably from 4.1 to 16.4% by weight of tin, calculated as SnO.

4. CeO 2 4. The glass according to claim 1, wherein the molar ratio of cerium, calculated as C(OH), to tin, calculated as SnO, is in the range of from 1.5:1 to 1:1.5, in particular from 1.2:1 to 1:1.2, preferably from 1.1:1 to 1:1.1, and more preferably is 1.0:1.

0.

5. 1.4 to 4.0% by weight, and particularly preferably 1.9 to 3.1% by weight of Li 2 The glass according to any one of claims 1 to 4, which contains O.

6. 6. The glass according to claim 1, which contains 0.4 to 2.4% by weight, in particular 0.6 to 1.9% by weight and particularly preferably 0.8 to 1.6% by weight of fluorine.

7. The indicated amounts of the following alkali metal oxides: Ingredients Weight% K 2 O 2.0~7.9 Especially 2.5 to 7.3 Particularly preferably, 2.9 to 6.9 Na 2 O3.8~8.0 Especially 4.4 to 7.4 Particularly preferably, 4.8 to 7.0 The glass according to any one of claims 1 to 6, comprising at least one, preferably all, of:

8. The indicated amounts of oxides of the following divalent elements Me II O: Ingredients Weight% CaO 0.8-2.5 Especially 1.0 to 2.0 Particularly preferably, 1.2 to 1.7 SrO 1.0~3.0 Especially 1.3 to 2.6 Particularly preferably, 1.6 to 2.3 ZnO 1.4~4.0 Especially 1.9 to 3.6 Particularly preferably, 2.3 to 3.3 MgO 0-1.0 Preferably 0 to 0.6 Especially 0 to 0.4 Particularly preferably, 0.1 to 0.4 The glass according to any one of claims 1 to 7, comprising at least one, preferably all, of:

9. Oxides of the following trivalent elements in the amounts indicated: Ingredients Weight% <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 245~7.3 Especially 2.8 to 6.8 Particularly preferably 3.2 to 6.3 B 2 O 3 1.0~4.5 Especially 1.3 to 4.1 Particularly preferably, 1.6 to 3.7 9. The glass according to claim 1, comprising at least one, preferably all, of:

10. The indicated amounts of oxides of the following tetravalent elements Me IV O 2 : Ingredients Weight% TO 2 0~2.2 Especially 0 to 1.7 Particularly preferably, 0.1 to 1.4 ZrO 2 0~1.2 Preferably 0.1 to 1.2 Especially 0.2 to 0.9 Particularly preferably, 0.4 to 0.6 10. The glass according to claim 1, comprising at least one, preferably all, of:

11. Oxides of pentavalent elements Me V 2 O 5 in an amount of 0 to 10.0% by weight, in particular 0 to 8.0% by weight, preferably 1.0 to 7.0% by weight, more preferably 2.0 to 6.8% by weight, and particularly preferably 3.0 to 6.5% by weight, wherein said Me V 2 O 5 Especially P 2 O 5 , Ta 2 O 5 and / or Nb 2 O 5 The glass according to any one of claims 1 to 10, wherein the glass is selected from

12. The following ingredients in the amounts indicated: Ingredients Weight% Yes 2 38.00~68.00 CeO 2 Cerium calculated as 4.0-23.0 Tin calculated as SnO 3.0-18.0 Li 2 O 1.0~5.0 <h2 style=";text-align:left;direction:ltr">Al<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> 245~7.3 Na 2 O3.8~8.0 K 2 O 2.0~7.9 CaO 0.8-2.5 SrO 1.0~3.0 ZnO 1.4~4.0 B 2 O 3 1.0~4.5 F 0.4 to 2.4 ZrO 2 0~1.2 MgO 0-1.4 TO 2 0~3.0 The glass according to any one of claims 1 to 11, comprising at least one, preferably all, of:

13. Glasses and glass ceramics comprising the cerium- and tin-containing glass according to any one of claims 1 to 12, preferably in an amount of 0.1 to 60% by weight, in particular 1 to 58% by weight, preferably 5 to 56% by weight, more preferably 10 to 54% by weight and particularly preferably 15 to 52% by weight.

14. Process for preparing the glass according to any one of claims 1 to 12, in which the tin is used at least partly in divalent form, in particular as SnO.

15. 15. The process according to claim 14, wherein the starting materials of the components of the glass are melted at a temperature of 1400° C. to 1700° C., in particular 1450 to 1600° C. and particularly preferably 1500° C., preferably for 20 minutes to 10 hours.

16. 13. Use of the glass according to any one of claims 1 to 12 as a mixture component for adjusting the fluorescence of glasses or glass ceramics.

17. 14. Use of a glass according to any one of claims 1 to 13 as a dental material, in particular for coating dental restorations, wherein the glass is applied to a substrate material and together with the substrate material is subjected to a heat treatment, preferably at a temperature of at least 600°C, in particular from 600 to 1150°C and particularly preferably from 700 to 1000°C.

18. 14. A process for coating dental restorations, in which a glass according to any one of claims 1 to 13 is applied to a substrate material and submitted together with said substrate material to a heat treatment, preferably at a temperature of at least 600°C, in particular 600 to 1150°C and particularly preferably 700 to 1000°C.

Citation Information

Patent Citations

  • Method for the preparation of lithium silicate glasses and lithium silicate glass ceramics

    EP2944619A1

  • Fluorescent glass ceramics and glasses containing cerium and tin

    EP3696149A1

  • Fluorescent glass ceramics and glasses containing europium

    EP3696150A1

  • Lithium silicate low quartz glass ceramics

    WO2017032745A1